2022
DOI: 10.1097/bpo.0000000000002061
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Artery of Ligamentum Teres in Revascularization in Legg-Calve-Perthes Disease

Abstract: Introduction: A recent cadaveric study supported that most immature hips are supplied by the artery of ligamentum teres and suggested this medial vascular source may influence the pattern of revascularization in Legg-Calve-Perthes disease (LCPD). The purposes of this study were to characterize the perfusion pattern of the capital femoral epiphysis and determine the role of the artery of ligamentum teres in early revascularization of LCPD. Methods: Retrospective review of perfusion magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Avascular necrosis of the femoral head (ANFH) is a common orthopedic disease characterized by bone cell apoptosis due to impaired blood supply to the femoral head, structural changes in the bone trabeculae, bone collapse, femoral head deformation, and ultimately irreversible changes, such as bone destruction and joint space narrowing, occur. [ 1 , 2 ] Epidemiological studies have shown that in the United States, there are over 25 000 new cases of ANFH annually, accounting for 14.9% of the approximately 480 000 total hip replacement surgeries performed each year. [ 3 ] Early ANFH symptoms are usually not obvious, and some patients have mild hip pain, followed by progression to joint mobility disorders, walking difficulties, secondary osteoarthritis, and eventually even joint replacement surgery, which places a heavy burden on patients and families.…”
Section: Introductionmentioning
confidence: 99%
“…Avascular necrosis of the femoral head (ANFH) is a common orthopedic disease characterized by bone cell apoptosis due to impaired blood supply to the femoral head, structural changes in the bone trabeculae, bone collapse, femoral head deformation, and ultimately irreversible changes, such as bone destruction and joint space narrowing, occur. [ 1 , 2 ] Epidemiological studies have shown that in the United States, there are over 25 000 new cases of ANFH annually, accounting for 14.9% of the approximately 480 000 total hip replacement surgeries performed each year. [ 3 ] Early ANFH symptoms are usually not obvious, and some patients have mild hip pain, followed by progression to joint mobility disorders, walking difficulties, secondary osteoarthritis, and eventually even joint replacement surgery, which places a heavy burden on patients and families.…”
Section: Introductionmentioning
confidence: 99%